1999
DOI: 10.1084/jem.189.11.1699
|View full text |Cite
|
Sign up to set email alerts
|

Exercise Provides Direct Biphasic Cardioprotection via Manganese Superoxide Dismutase Activation

Abstract: Epidemiologic investigations have shown that exercise reduces morbidity and mortality from coronary artery disease. In this study, using a rat model, we attempted to determine whether exercise can reduce ischemic injury to the heart and elucidate a mechanism for the cardioprotective effect of exercise. Results showed that exercise significantly reduced the magnitude of a myocardial infarction in biphasic manner. The time course for cardioprotection resembled that of the change in manganese superoxide dismutase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
336
7
4

Year Published

2002
2002
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 317 publications
(360 citation statements)
references
References 48 publications
13
336
7
4
Order By: Relevance
“…During higher intensities of exercise, whole-body and muscle oxygen consumption increases up to 20-and 100-fold respectively [45], leading to increased release of superoxide from the mitochondrial electron transport chain. As Cu/Zn-SOD is downregulated with increased exposure to oxygen [46], upregulation of MnSOD under these conditions is common across various tissues [5,47,48] and may play a role in compensating a lack of Cu/Zn-SOD upregulation, thus providing greater protection by preventing formation of nitrotyrosine and protein oxidation, as shown in our study.…”
Section: Discussionsupporting
confidence: 68%
“…During higher intensities of exercise, whole-body and muscle oxygen consumption increases up to 20-and 100-fold respectively [45], leading to increased release of superoxide from the mitochondrial electron transport chain. As Cu/Zn-SOD is downregulated with increased exposure to oxygen [46], upregulation of MnSOD under these conditions is common across various tissues [5,47,48] and may play a role in compensating a lack of Cu/Zn-SOD upregulation, thus providing greater protection by preventing formation of nitrotyrosine and protein oxidation, as shown in our study.…”
Section: Discussionsupporting
confidence: 68%
“…69 Various interventions such as administration of antioxidant vitamins and antihypertensive agents and exercise training have been shown to enhance the protein levels and enzymatic activities of SODs, such as Cu/Zn SOD and Mn SOD, in the vascular endothelium and smooth muscle cells of the aorta in various animal models. 70,71 In the vasculature of humans, approximately 50% of total SOD is extracellular SOD. 72 Fukai et al 73 demonstrated that exercise for 3 weeks increased eNOS and extracellular SOD protein levels in wildtype mice but had no effect on extracellular SOD protein levels in eNOS-knockout mice and that the effect of endothelium-derived NO on extracellular SOD protein level is mediated by the cGMP/protein kinase G-dependent pathway.…”
Section: Endothelial Function and Hypertension In Agingmentioning
confidence: 99%
“…Exercise also elicits two windows of protection. This is best exemplified in the study by Yamashita et al (75) in which rats were subjected to treadmill running for 30 min, after which different groups were subjected to myocardial ischemia from 30 min to 72 h after the end of the training. The authors found that exercise reduced the degree of myocardial infarction in a biphasic manner.…”
Section: Putative Cardioprotective Mechanisms Of Exercisementioning
confidence: 99%
“…In most cases, studies designed to test the protective effects of exercise involve training for 3 days, 7 days, or up to 12 wk, and then within 24 h of the last exercise session the animals were subjected to myocardial ischemia. Yamashita et al (75) noticed that delaying the time between a single treadmill training session (30 min) and the onset of ischemia to 36, 48, or even 60 h resulted in similar degrees of infarct size reduction compared with animals subjected to ischemia right after the training session. This was further confirmed by in a study by Lennon et al (44).…”
Section: No Metabolites Mediate the Cardioprotective Effects Of Exercisementioning
confidence: 99%